EVALUATED EFFECTS OF THE TREATMENT WITH IMATINIB OF CHRONIC MYELOID LEUKEMIA PATIENTS WITH ADDITIONAL CYTOGENETIC ABNORMALITIES IN HEMATOLOGY AND BLOOD TRANSFUTION CENTER, BACHMAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluated effects of the treatment with imatinib of chronic myeloid leukemia patients with additional cytogenetic abnormalities (ACAs) since 2012 to March 2025.Subjects: Patients were diagnosed chronic myeloid leukemia (CML) in chonic phase with additional cytogenetic abnormalities and were treated with imatinib in Hematology and Blood transfution center Bachmai Hospital from 2012 to 3/2025.Method: Retrospective cohort study.Results: At the 35 patients CML with ACAs were treated with imatinib, the most common additional cytogenetic abnormalities include additional Ph translocation (34,2%), complex karyotype (28,6%), trisomy 8 (11,4%) and second Ph (11,4%). Rate of complete hematologic response after 3 months was 91,4%. Rate of complete cytogenetic response after 12 months was 42,9%. Rate of major molecular response was 48,6%. The survival rate was 51,4%. The overall 5-years relative survival rate was 47,1%.Conclusion: The patients with ACAs were treated with imatinib had rate of complete hematologic response after 3 months was 91,4%, rate of complete cytogenetic response after 12 months was 42,9%, rate of major molecular response was 48,6%, the overall 5-years relative survival rate was 47,1%.
Keywords: chronic myeloid leukemia, additional cytogenetic abnormalities, imatinib